2015
DOI: 10.1177/1010539515583332
|View full text |Cite
|
Sign up to set email alerts
|

Frail Elders in an Urban District Setting in Malaysia

Abstract: In the past decade, the population in Malaysia has been rapidly ageing. This poses new challenges and issues that threaten the ability of the elderly to independently age in place. A multistage cross-sectional study on 789 community-dwelling elderly individuals aged 60 years and above was conducted in an urban district in Malaysia to assess the geriatric syndrome of frailty. Using a multidimensional frailty index, we detected 67.7% prefrail and 5.7% frail elders. Cognitive status was a significant correlate fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 43 publications
3
25
6
Order By: Relevance
“…In this study, the prevalence of frailty syndrome among the Malay community-dwelling elderly in the area of Kuala Nerus, Terengganu was 18.3%, based on Fried's criteria. This finding was quite higher than the previous local study (Sathasivam et al, 2015) where the prevalence found was 5.7% using the Frailty Index among 789 urban community-dwelling elderlies aged 60 years and above in Malaysia. This range might be due to the difference of frailty definition, measurement instruments, and the criteria used (Sathasivam et al, 2015), which this study used Frailty Phenotype to define frailty syndrome.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…In this study, the prevalence of frailty syndrome among the Malay community-dwelling elderly in the area of Kuala Nerus, Terengganu was 18.3%, based on Fried's criteria. This finding was quite higher than the previous local study (Sathasivam et al, 2015) where the prevalence found was 5.7% using the Frailty Index among 789 urban community-dwelling elderlies aged 60 years and above in Malaysia. This range might be due to the difference of frailty definition, measurement instruments, and the criteria used (Sathasivam et al, 2015), which this study used Frailty Phenotype to define frailty syndrome.…”
Section: Discussioncontrasting
confidence: 72%
“…This finding was quite higher than the previous local study (Sathasivam et al, 2015) where the prevalence found was 5.7% using the Frailty Index among 789 urban community-dwelling elderlies aged 60 years and above in Malaysia. This range might be due to the difference of frailty definition, measurement instruments, and the criteria used (Sathasivam et al, 2015), which this study used Frailty Phenotype to define frailty syndrome. Meanwhile, it would be consistent with the previous study that found the prevalence of frailty is 15.2% in people of 60 years of age and older in the rural areas in Colombia.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Despite the growing attention, evidence on frailty in Malaysia is scarce and limited. One study reported a 5.7% prevalence of frailty in Malaysia using the multidimensional approach [ 18 ], while another study using Fried’s phenotype reported an 8.9% prevalence [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional research in an urban district of Malaysia evaluated the frailty syndrome in 789 elderly people (age ≥60 years old), living in the community. Those classified as non-frail were 26.6% (18) . In the US, the multicentre longitudinal population study with 7,439 elderly found 39.2% non-frail people.…”
Section: Discussionmentioning
confidence: 99%